First at the South Pole: the production of geographical 'matters of fact' during the Norwegian antarctic expedition, 1910-12 - Schillings, Pascal (DEU, 2016)
"This article seeks to open a so-called black box. It asks how the information that Roald Amundsen reached the South Pole in December 1911 became accepted as a 'matter of fact' that found its way into most overviews of the 19th century. To open this black box, the article examines the techniques and strategies that the Norwegian Antarctic expedition of 1910 to 1912 applied to produce its data. It argues that the Norwegian expedition applied at least three different techniques: optical instruments were used to come as close to the pole as possible and encir-cle it; landmarks were left around the pole to turn the British expedition that followed the Norwegians at the pole into eye-witnesses; in Europe, the tables of geographical data that Amundsen had noted in his journal were recalculated to affirm its accuracy. Two observations follow from the focus on the expedition’s practices: firstly, the Antarctic landscape and its climate were vital actors in the production of geographical data in the Antarctic. Secondly, the Norwegian strategy was markedly more defensive than the black-boxed sentence about its presence at the pole suggests: It relied on a combination of techniques to ascertain, and aimed at proximity rather than a claim to have been at the pole." (author's abstract)